Mulheres na agroecologia : um estudo bibliométrico - Iyusuka, Sheyla Saori (2015)
The sexual division of work brings the forms of unequal as if establish relations of organization, production and conduct of choices in the forms of land use. The presence of women in the scenario of agriculture is still marginalized and amended as aid to work of the men, which are considered the main force of productive unit, and in extension activities to domestic work - as vegetable gardens, small livestock and other activities that involve the backyard. From addition, in rural studies, is a great challenge to incorporate the woman as the subject and focus of research. This article understands the importance of giving continuity and visibility to the studies and research that involve the theme of women and gender in agriculture, in particular in the area of knowledge of agroecology. This way, it was proposed a bibliometric analysis of the studies presented in the Brazilian Congresses of Agroecology (CBAs). Whereas the various contributions of different areas of knowledge in agroecology, bibliometrics can provide important information on the directions of studies and research in this area in Brazil. To analyze the data and the content of the abstracts expanded with the theme of women and gender, it was chosen to organize them through a filter with the following terms: gender, women, peasant, rural women, workers, women, farmers, producers, the ospreys, seated and garbage collectors. The summaries selected from the filter were organized through the following metadata: Title, Authorship, Affiliation, Year of publication, Abstract and Keyword. In this article we managed to analyze the authorship and affiliation, showing how each state/region of Brazil has influenced on publications during the twelve years of CBA. Was perceived also as the theme was growing during the editions of the event and, at this moment, it was studied the trajectory of groups and institutions in the various spaces of agroecology, and as v influenced the universities, technical assistance and rural extension and nongovernmental organizations with the theme.